Incorporation TACOM and SPAR-H into the operating procedure of nuclear power plants. (April 2018) - Zhao, Xiaosong; Zhang, Rui; Zhao, Shumeng; Wu, You; He, Zhen
Highlights: A model is constructed incorporation TACOM and SPAR-H into NPPs. The HEP is predicted with TACOM and SPAR-H method in main control room of NPPs. The result shows the method can achieve a more accurate prediction of the HEP. When the complexity of tasks is less difference, the result of the improved method will be more accurate than the SPAR-H method. Abstract: The digital control system has improved the equipment reliability and the productivity of nuclear power plants (NPPs) greatly. However, the human error in main control room of digital control systems has become a major influence for the safety and economic efficiency. Based on the task complexity and human reliable analysis, this study analyzes the procedural tasks in the main control room. Standardized Plant Analysis Risk Human Reliability Analysis (SPAR-H) method lacks cognitive activity analysis and the results are not accurate due to the subjective assessment of performance shaping factors (PSFs). The TACOM (Task Complexity) quantification method is then introduced to SPAR-H method to gain precise results. Finally, the steam generator tube ruptures is analyzed using the improved method and comparison is made between the result and empirical data. The result shows that the improved method can effectively identify task complexity factor to achieve a more accurate prediction of the human error probability, and the improvement of the prediction is significant to the safe operation of nuclear power plant. Moreover, the improved method can distinguish the tasks that with similar difficulties which is very important for the task selection in time-urgent situation.